PENGARUH HAMBATAN SAMPING AKIBAT AKTIVITAS PASAR TERHADAP KECEPATAN KENDARAAN DAN DERAJAT KEJENUHAN (STUDI KASUS PASAR LELEDE-RUAS JALAN ISMAIL MARZUKI) - ROHANI ROHANI; MADE MAHENDRA; IKA FEBRIANA PUTRI (SOSIAL SAINS DAN TEKNOLOGI, 2022)
Lelede Market is one of the markets in Cakranegara Mataram City which has high activity, the location of the market which is on the side of the road causes market visitors to use the shoulder of the road as a parking lot, and the high side barriers as a result of market activity causes vehicle speed to be low, so the travel time for taking the road is getting bigger.The purpose of this study was to determine the side resistance, speed and degree of saturation on the Ismail Marzuki road section and also to determine the effect of side resistance on the speed and degree of saturation using MKJI 1997.The results of the analysis on the Ismail Marzuki road when market activity has side resistance, speed and degree of saturation, respectively, are 1086.7 events/hour, 29.69 km/hour and 0.72. When there is no side drag market activity, the speed and degree of saturation are 794.2 events/hour, 33.28 km/hour and 0.43 respectively. The effect of side resistance on speed is 0.999 and the degree of saturation is 0.969 during market activity. When there is no market activity, side barriers affect the speed and degree of saturation by 0.979 and 0.975. So that the higher the value of the side resistance, the lower the speed, while the higher the value of the side resistance, the higher the degree of saturation.